Pemanfaatan Sampah Organik Sebagai Pupuk Cair Berbasis Effective Microorganism 4 (Em4) untuk Pertanian (Universitas Negeri Semarang, 2022)
Waste is a problem in its own community. Because of this, youth groups who care about the environment,